Depth of Formation of Specular Reflection of X-Rays and Neutrons and its Relationship with the Group Delay Time - Bushuev, V. A.; Frank, A. I.
The problem of the connection of the group delay time (GDT) with the depth in the medium at which the formation of specular reflection of X-rays and neutrons from a semi-infinite homogeneous medium with an ideally sharp interface in the regions up to the threshold of the total external reflection (TER) and above this threshold is discussed. The article has a discussion character and is based on materials that are not included in the review [1].
Keywords: Physics; Optics